The struggles of Tucuman students between two coups, 1966-1976 (Quinto Sol, 2021)
This article presents an analysis of the struggles of the student movement of the National University of Tucumán between the coup d'etats of 1966 and 1976, operationalized as social confrontations. The forms of action, the organizations, the claims, the action scenarios and the alliances developed by the Tucumán's students are considered thereby, characterizing the cycles of local conflict and their place in the national context. To do this analysis we codify a database of student struggle from newspapers.
Keywords: student movements; National University of Tucuman; coup d’etat; rebellions